Monumenti della food security. Granai e città capitali al tramonto dell’Antico Regime - Clemente, Alida (OS. Opificio della Storia, 2023)
Despite the progressive liberalisation of the grain trade, monumental public buildings for the storage of grain were erected in numerous European and Mediterranean capitals between the eighteenth and nineteenth centuries. The essay illustrates some examples and highlights the specificity of late modern technical and political approaches to the management of stocks, which, far from appearing as remnants of mediaeval and early modern annona policies, reconfigure the problems of grain conservation and the function of public granaries within a framework of political centralisation, macroeconomic regulation and communication policy. Theoretically conceived as an instrument of intertemporal price arbitrage without interfering with the functioning of the market, these mammoth buildings, which dominate the urban fabric with their monumentality, seem to fulfil above all a symbolic function of food security, in example as an anti-panic device in times of food crises.